Computational analysis and in vitro investigation on Citrus flavonoids for inflammatory, diabetic and AGEs targets - Ali MuhamedAhmed; Zahid Rasul Niazi; Muhammad Hanif; Abdul Rafey; Kashif Iqbal; Luc Pieters; Adnan Amin (Universidade de São Paulo, 2023)
Abstract Flavonoids are a diverse class of polyphenolic substances largely found in plants including citrus peels and are reported to posess a variety of biological activities. We investigated important flavonoids apigenin, hesperidin, narigin, quercetin and tangeritine against diabetes and associated conditions. In current project drug likeness, ADMET analysis, molecular docking and in vitro assays were performed. The apigenin, quercetin and tanagretin exhibited compliance with Lipinski's rule of five. The molecular docking analysis showed best fit in transcriptional regulator 3TOP and 1IK3 in all tested compounds. During antioxidant assays, all flavonoids presented excellent activities. In the α-glucosidase assay, quercetin showed highest inhibition (76% at final concentration of 52 µg/ml) followed by tangeritin (73% at final concentration of 52 µg/ml). In case of 15-Lox assay, highest inhibition was seen in case of quercetin (75%) followed by apigenin (53%). In the AGEs assay, the quercetin showed 47% inhbition of protein cross link formation preceeded by the tenegretin exhited 37% inhibition. It was therefore concluded that tested flavonoids have significant activities in both in silico and in vitro models that is mainly due to differences in structural features and polar surface area.